2006
DOI: 10.1016/j.cub.2006.06.069
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Mitochondrial Chaperones Utilized in Fe-S Cluster Biogenesis

Abstract: Biogenesis of Fe-S clusters is an essential process [1]. In both Escherichia coli and Saccharomyces cerevisiae, insertion of clusters into an apoprotein requires interaction between a scaffold protein on which clusters are assembled and a molecular chaperone system--an unusually specialized mitochondrial Hsp70 (mtHsp70) and its J protein cochaperone [2]. It is generally assumed that mitochondria inherited their Fe-S cluster assembly machinery from prokaryotes via the endosymbiosis of a bacterium that led to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 33 publications
5
93
0
1
Order By: Relevance
“…In contrast, a chimera having the mtHsp70 PBD fused to an HscA ATPase domain was completely soluble upon overexpression in E. coli. These findings are consistent with studies performed by Craig and coworkers (2), which showed that an mtHsp70 truncation mutant having ATPase , ⌬v is the observed change in rate, and ⌬v max is the maximal rate obtained by extrapolating to infinite Hep concentration. The data are fit to a hyperbolic saturation function assuming a maximal stimulation for 70…”
Section: Discussionsupporting
confidence: 82%
“…In contrast, a chimera having the mtHsp70 PBD fused to an HscA ATPase domain was completely soluble upon overexpression in E. coli. These findings are consistent with studies performed by Craig and coworkers (2), which showed that an mtHsp70 truncation mutant having ATPase , ⌬v is the observed change in rate, and ⌬v max is the maximal rate obtained by extrapolating to infinite Hep concentration. The data are fit to a hyperbolic saturation function assuming a maximal stimulation for 70…”
Section: Discussionsupporting
confidence: 82%
“…The representative of all major families such as Hsp70 and its co-chaperones, Hsp60 and Hsp100 (Hsp78 in mitochondria), are represented and they display a broad specificity. However, more specialized chaperones such as those acting in the iron-sulfur cluster assembly pathway are also known (89,90). It is less clear how proteins in the IMS are folded and assembled into the functional units.…”
Section: Assembly Of Mitochondrial Proteinsmentioning
confidence: 99%
“…2). The dissociation of the Fe/S cluster from Isu1 is facilitated by a dedicated Hsp70 chaperone system comprised of the Hsp70 ATPase Ssq1 (human mortalin), the DnaJ-like cochaperone Jac1 (human Hsc20), and the nucleotide exchange factor Mge1 (human GRPE-L1/2) (Schilke et al 2006;Vickery and Cupp-Vickery 2007;Uhrigshardt et al 2010). The molecular mechanism of the chaperones in this reaction is strikingly similar to Hsp70 chaperone function in protein folding, and has been worked out in both bacteria and yeast (Vickery and Cupp-Vickery 2007;Kampinga and Craig 2010).…”
Section: Biogenesis Of Mitochondrial Fe/s Proteins By the Isc Assemblmentioning
confidence: 99%